Advances in cement technology : critical reviews and case studies on manufacturing, quality control, optimization and use - Ghosh, S. N. (Pergamon Press, 1983)
Advances in Cement Technology: Critical Reviews and Case Studies on Manufacturing, Quality Control, Optimization and Use is a collection of articles that reviews the important aspects of the science and technology of cement. The book presents 20 papers that cover areas such as geology, raw materials, manufacture, chemistry, additions, admixtures, and industrial wastes.